Conceptualization and measurement of physiologic health for adults. Vol. 1, Overview of chronic disease in a general adult population - Lohr, Kathleen N., 1941-; Kamberg, Caren J., 1946-; Keeler, Emmett B.; Goldberg, George A., 1941-; Brook, Robert H. (Robert Henry), 1943-; Rand eBooks (Santa Monica, CA : RAND, 1986)
This report serves as the overview volume for a series (R-2262-HHS) on the conceptualization and measurement of health for adults in the RAND Health Insurance Experiment (HIE), a large-scale, controlled trial in health care financing that ran in the field from November 1974 through January 1982. The report combines information from the HIE on the prevalence, associated effects, and use of medical care for several important chronic conditions or impairments. The focus is on a sample of persons 18 to 61 years of age in the United States in the mid-1970s, when the HIE was getting under way. The sections of the report describe the data sources and analytic techniques used; present results of special analyses, with findings about prevalence, use of medical care, and impact of diseases; and discuss the implications of the findings.
"November 1986."
Includes bibliographical references (p. 31-35).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Chronic diseases -- United States -- Statistics; Health status indicators -- United States; Health surveys -- United States; Insurance, Health -- United States -- Statistics; Chronic Disease -- Adult; Health Surveys -- United States; Insurance, Health -- United States; Electronic books